Sexual and reproductive health needs and practices of female sex workers in Papua New Guinea: findings from a biobehavioral survey Kauntim mi tu ('Count me too') - Damian Weikum; Angela Kelly-Hanku; Ruthy Neo-Boli; Herick Aeno; Steven G. Badman; Lisa M. Vallely; Barne Willie; Martha Kupul; Parker Hou; Angelyn Amos; Rebecca Narokobi; Simon Pekon; et al. (BMC, 2022)
Abstract Background Little research has explored the sexual and reproductive health (SRH) experience of female sex workers (FSW), including girls aged < 18 years who are commercially sexually exploited (CSE), in Papua New Guinea (PNG). This paper describes the SRH history of FSW and CSE girls and factors associated with their use of moderately or highly effective contraceptive methods in three settings in PNG. Methods From 2016 to 2017, respondent-driven sampling (RDS) surveys were conducted among FSW and CSE girls in Port Moresby, Lae, and Mt. Hagen. FSW and CSE girls who were born female, aged ≥12 years, sold or exchanged vaginal sex in the past 6 months, spoke English or Tok Pisin, and had a valid RDS study coupon were eligible to participate. Interviews were conducted face-to-face and participants were offered rapid routine HIV and syphilis testing. Survey logistic regression procedures were used to identify factors associated with the use of moderately or highly effective contraceptive methods. Weighted data analysis was conducted. Results A total of 2901 FSW and CSE girls (Port Moresby, 673; Lae, 709; and Mt. Hagen, 709) were enrolled. The proportion using moderately or highly effective contraceptive methods was 37.7% in Port Moresby, 30.9% in Lae, and 26.5% in Mt. Hagen. After adjusting for covariates, factors significantly associated with the use of moderately or highly effective contraceptive methods in Port Moresby were being age 20-24, being married, being divorced or separated, having one or more dependent children, being away from home for more than 1 month in the last 6 months, and having tested HIV negative. No factors were significantly associated in Lae or Mt. Hagen. ANC attendance amongst FSW and CSE girls who gave birth in last 3 years was highest in Port Moresby at 91.2%. HIV testing was inconsistently and inadequately offered at ANC across the three cities. Conclusions Kauntim mi tu provides much-needed insight into the SRH experiences of FSW and CSE girls in PNG, where their use of moderately or highly effective contraceptive methods is low. We hope to shed light on the complicated reality they face due to illegality of sex work and multitude of complex healthcare experiences.